1994
DOI: 10.1111/j.1439-0388.1994.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of meat production by embryonic muscle formation – a review

Abstract: The biological basis for meat production in livestock animals is localized in the muscles, where lean meat production is under the genetic control of tissue-specific and more ubiquitously operating genes. The muscle tissue-specific MyoD gene family is at the centre of the genetic regulation of myoblast proliferation and differentiation into myofibres. The regulation of embryonic muscle tissue formation (development) by the MyoD genes is duscussed in the context of livestock animals used in meat production. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 42 publications
0
14
0
2
Order By: Relevance
“…Within a few thousand bp, the recombination percentage will be almost zero. So a PCR-RFLP detection of gene-specific haplotypes allows a fast detection of functional polymorphisms in which the same gene is involved (Te Pas and Visscher 1994). We describe the localization of four haplotypes within the porcine MYOG gene locus that can be detected by PCR-RFLPs with MspI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within a few thousand bp, the recombination percentage will be almost zero. So a PCR-RFLP detection of gene-specific haplotypes allows a fast detection of functional polymorphisms in which the same gene is involved (Te Pas and Visscher 1994). We describe the localization of four haplotypes within the porcine MYOG gene locus that can be detected by PCR-RFLPs with MspI.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the sequence we describe here with another recently reported sequence of the porcine MYOG gene (Briley et al 1995) also shows differences only outside these regions (see the EMBL data base entry X89007). Association studies require the genetic screening of many animals, showing the need for fast methods like PCR-based tests, rather than time-consuming methods such as Southern-RFLP or sequencing (Te Pas and Visscher 1994). Fast and easily detectable PCR-RFLP tests detecting polymorphic sites near to, but outside the coding and regulatory regions of a gene can be associated with functional sequence divergence of a gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MyoG has a central position within the MyoD gene family, not only because MyoG expression abrogates myoblast proliferation potential and regulates the differentiation of mononucleated myoblasts into multinucleated myofibers (Wright et al, 1989;Weintraub et al, 1991;Pas and Visscher, 1994), but also due to MyoG being the only member of the MyoD gene family that is expressed in all myogenic cell lines (Anton et al, 2002). The MyoG gene regulates the expression of muscle-specific genes, which encode several proteins that control the formation and apoptosis (or necrosis) of muscle fibers (Olson, 1990;te Pas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (1998) found significant effects of FSHB gene on pig litter size in the population of Landrace, Yorkshire and Yorkshire hybrids crossed with the Erhualian breed. The myogenin gene (MYOG) plays a role during the terminal transformation of myoblasts into myofibres (Te Pas and Visscher, 1994). The effect of MYOG gene on reproductive traits was reported only by Horák et al (2004).…”
mentioning
confidence: 99%